2001
DOI: 10.1577/1548-8454(2001)063<0052:pacofo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Pigmentation and Composition of Flesh of Atlantic Salmon Fed Diets Supplemented with the YeastPhaffia rhodozyma

Abstract: In a pigmentation trial, Atlantic salmon Salmo salar in ocean pens were fed diets supplemented with the red yeast Phaffia rhodozyma, a control diet supplemented with synthetic astaxanthin, and a nonpigmented control diet. Yeast diets contained spray‐dried untreated P. rhodozyma, heat‐treated and spray‐dried P. rhodozyma, and heat‐treated and chemically treated spray‐dried P. rhodozyma. Growth, weight, and fork length of all fish increased linearly with feeding and were not significantly different at the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…A formulation of P. rhodozyma cells blended with ethoxyquin, lecithin and saZower oil prior to drying also increased astaxanthin deposition in salmonid Wsh Xesh and rainbow trout Xesh when supplied in feed as an additive [94]. Whyte and Sherry [160] and Fleno et al [113] observed that the astaxanthin concentration was not signiWcantly diVerent between Wsh (Atlantic salmon) fed diet supplemented with spray-dried ruptured cells P. rhodozyma and those fed the synthetic astaxanthin diet. The astaxanthin-rich oil produced by a process for extracting carotenoids from P. rhodozyma biomass, was directly used as an additive to salmonid Wsh feed [161].…”
Section: Carotenoid-synthesizing Yeasts-directions For Their Usementioning
confidence: 99%
“…A formulation of P. rhodozyma cells blended with ethoxyquin, lecithin and saZower oil prior to drying also increased astaxanthin deposition in salmonid Wsh Xesh and rainbow trout Xesh when supplied in feed as an additive [94]. Whyte and Sherry [160] and Fleno et al [113] observed that the astaxanthin concentration was not signiWcantly diVerent between Wsh (Atlantic salmon) fed diet supplemented with spray-dried ruptured cells P. rhodozyma and those fed the synthetic astaxanthin diet. The astaxanthin-rich oil produced by a process for extracting carotenoids from P. rhodozyma biomass, was directly used as an additive to salmonid Wsh feed [161].…”
Section: Carotenoid-synthesizing Yeasts-directions For Their Usementioning
confidence: 99%
“…2005), provide desirable flesh colouration (Johnson et al. 1977, 1980; Whyte & Sherry 2001; Storebakken et al. 2004), and may possibly serve as an alternative protein source to fish meal (Dabrowksi et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all of the effects of yeast in the diet of cultured fish have been clearly beneficial (Rumsey et al. 1991; Whyte & Sherry 2001; Li et al. 2005; Lim et al.…”
Section: Introductionmentioning
confidence: 99%
“…The relative distribution of esters and optical isomers in some organisms is shown in table 3. The level of astaxanthin detected in the mangrove floral species of Indian Sundarbans is less than the existing natural mega-reservoir of astaxanthin like Phaffia rhodozyma [19][20] and Haematococcus pluvialis [21]. However considering the huge biomass of mangrove leaves in and around the area of Sundarban Biosphere Reserve (SBR), the standing stock of the carotenoid pigment has high probability to reach the point of compensation (requirement), provided few back-up nurseries in the region for extraction of bioactive substances are maintained.…”
Section: Resultsmentioning
confidence: 99%